Steady State Multiplicity In The Reactive Distillation Of Methyl Tert-Butyl Ether (MTBE) Synthesis: Stability Analysis - Adnan, Fietriey Atiera Shahida (Universiti Sains Malaysia, 2021)
Reactive distillation (RD) has garnered a lot of attention due to its tremendous potential for process intensification. Due to that, the methyl tert-butyl ether (MTBE) synthesis in reactive distillation (RD) column was studied and an equilibrium model was developed by using Aspen Plus V10. The proposed model was validated by comparing the simulation results with the published simulation results from the literature. The model obtained high isobutene conversion and MTBE purity for heterogenous catalyzed system, which is desirable in the industrial MTBE production process. The comparisons on temperature profiles and liquid composition profile of RD column also yielded promising results. The proposed model can be used as a tool for the analysis of multiple steady state in RD column of MTBE. It is concluded that only single steady state of MTBE synthesis that can be found when using the same column configuration in Aspen Plus V10. Sensitivity analysis is conducted to study the influence of reflux ratio on the isobutene conversion. From this analysis, it was shown that MTBE purity and isobutene conversion were maximum at reflux ratio of 7. Stable reactive distillation of MTBE can be achieved since the equilibrium modelling has developed higher steady state solution.